Public Reporting System for Assessing Public Awareness on Vector Borne Diseases by Digital Crowdsourcing - Leong, Chin Jian; Aziman, Abdullah (2016)
This project is about to assessing the awareness of public to Zika virus. For this purpose, digital crowdsourcing is the method chosen to be used. Bydoing this, a Public Reporting System is to be introduced since the availability of mobile devices is very commonly to everyone in nowadays. Therefore, digital crowdsourcing through the use of mobile device application is one of the most effective approach.